A NEW ELECTROCHEMICAL SENSOR BASED ON MODIFIED CARBON NANOTUBE-GRAPHITE MIXTURE PASTE ELECTRODE FOR VOLTAMMETRIC DETERMINATION OF RESORCINOL - Jg, Manjunatha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: A new carbon nanotube (CNT)-graphite mixture paste electrode modified by Sodium dodecyl sulfate (SDS) surfactant (SDSMCNTGMPE) was prepared and applied for sensitive electrochemical determination of resorcinol (RS). Method: Cyclic voltammetry, variable pressure scanning electron microscopy, and differential voltammetry were employed for the surface analysis of the bare CNT-graphite mixture paste electrode and SDSMCNTGMPE. Comparison between the unmodified electrode and modified electrode, the modified electrode oxidation peak current significantly improved. The effects of the pH, scan rate, and concentration of RS on the peak current were investigated. Results: Results indicated that the peak current of RS is highest in 0.2 M pH 7.0 phosphate buffer solutions and that the electrode reaction corresponds to a rate controlled process. Under optimized experimental conditions, the oxidation peak current of RS was linear over a concentration range of 2×10−6 to 1.0×10−3 M with a detection limit of 5.8×10−6 M and quantification limit of 19×10−6 M. Conclusion: The prepared sensor also shows other features such as good stability, reproducibility and repeatability. The proposed sensor exhibits good application toward the detection of RS in commercial RS lotion samples.